2019
DOI: 10.2478/hukin-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Successful Offensive Play Patterns by the Spanish Soccer Team

Abstract: Victory is the ultimate aim in soccer and therefore when a team wins an elite European or world championship, attempts will invariably be made to emulate the winning team’s style of play. In this study, we performed an in‐depth analysis of play by the Spanish soccer team during the 2012 UEFA European Championship, where it was crowned champion. Using observational methodology and T‐pattern analysis, we identified hidden patterns of play that ended in a goal for the Spanish team. A generalizability coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…Secondly, the bivariate analysis has confirmed that winning or successful teams perform significantly more possessions of the ball than unsuccessful or loser teams. These results seem to coincide with previous studies in men's football (Casal et al, 2017;Amatria et al, 2019a), although the results should still be taken with caution since the results are still inconclusive (Jones et al, 2004;.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Secondly, the bivariate analysis has confirmed that winning or successful teams perform significantly more possessions of the ball than unsuccessful or loser teams. These results seem to coincide with previous studies in men's football (Casal et al, 2017;Amatria et al, 2019a), although the results should still be taken with caution since the results are still inconclusive (Jones et al, 2004;.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the results suggest that the tactical intention to progress or preserve is also significantly influenced by the match status in unsuccessful teams. This is something of value from a tactical point of view, because one of the most important decisions that teams must make when recovering the ball is whether to keep the same, by means of a gradual construction of the attack, or to progress directly toward the rival goal (Casal et al, 2017;Amatria et al, 2019a). As long as they opt for one option or another, in unsuccessful teams this will have a very important impact on the ball possession depending on whether it is winning, drawing, or losing.…”
Section: Discussionmentioning
confidence: 99%
“…As a general profile, the differences seem to indicate that LFBs are players who develop less combination play, although they have much more finishing and verticality. These results are in line with those described by Amatria et al., 39 who identified right-wing players with a recovery profile and left-wing players with an offensive profile. In the case of the left-wing players, they use one touch to develop walls, as well as dribbling as a means to overcome the defensive lines.…”
Section: Discussionsupporting
confidence: 93%
“…The quantitative data of the viewing sessions were entered into a free LINCE software package. LINCE software, only available to Windows operating system, is commonly used to analyse behaviour in sports [ 21 , 22 , 23 ] and allows simultaneous viewing and recording of behaviours while watching videos on a computer screen. The software also allows data to be exported in different formats for analysis.…”
Section: Methodsmentioning
confidence: 99%